Effect of impulse control disorders on disability and quality of life in Parkinson’s disease patients - Phu, Amy L.; Xu, Zheyu; Brakoulias, Vlasios; Mahant, Neil; Fung, Victor S.C.; Moore, Gregory De; Martin, Andrew; Starcevic, Vladan; Krause, Martin (Journal of clinical neuroscience, 2014)
Impulse control and related disorders (ICRD) are not uncommon in patients with idiopathic Parkinson’s disease (PD). The present study aimed to investigate the effects of ICRD on quality of life (QoL) and disability in PD. From two movement disorder clinics in Sydney, Australia, 100 consecutive patients with PD were included in the trial. The Unified Parkinson’s Disease Rating Scale (UPDRS), Mini Mental State Examination and the Parkinson’s Disease Questionnaire-39 were used to measure disease severity, cognition and disease-specific QoL. The diagnosis of ICRD was based on face-to-face structured clinical interviews by three psychiatrists with experience in ICRD using the Expanded Structured Clinical Interview for the Diagnostic and Statistical Manual IV for Obsessive-Compulsive Disorder Related/Spectrum Disorders. ICRD were present in 15% of our patient population, and had a negative impact on QoL and Activity of Daily Living (ADL) scores. After adjusting for the presence of major depressive disorders and PD duration, the effect on emotional wellbeing remained statistically significant (p<0.004). Disease duration also correlated with worse QoL and ADL scores. Major depression disorders reduced QoL but not ADL. Patients with ICRD tended to suffer more from depression than those without ICRD. There were no statistically significant differences in age, sex, major depressive disorders, PD duration, total levodopa equivalent daily dose, use of dopamine agonists, or UPDRS motor score between patients with and without ICDR.